Applications of pulsed USWR method for materials studies - Valič, Marko (Kovine zlitine tehnologije, 1999)
In this contribution some application possibilities for nondestructive following, in time domain, of the early hydration processes of hydraulic pastes and reaction hardening of selected materials with a new apparatus employing pulsed ultrasonic shear waves reflection (USWR) method are shown. The home-made apparatus USWR-2 Hardening meter is described. The sensitivity of the instrument to important parameters (rheology, composition, water content, fineness, particle size distribution, addition of additives, temperature, ageing) influencing a material behavior is eminent from the results obtained so far, offering several laboratory testing applications.
Keywords: ultrasound; ultrazvok; hidratacija; cement; strjevanje